Seeding the Garden - Danielle Treadwell; David Outerbridge; Tabitha Petri; James M. Stephens (EDIS)
Growing your own Florida vegetable garden can be a rewarding experience with a little planning. This 5-page publication of the UF/IFAS Horticultural Sciences Department presents an overview of proper seed selection and planting. It also provides best management practices, as well as relevant terms and methods, for seeding vegetables in home and community gardens. Written by Danielle Treadwell, David Outerbridge, Tabitha Petri, and James M. Stephens. https://edis.ifas.ufl.edu/vh026